Prevalence of thyroid dysfunctions in pregnant women: a prospective study in a tertiary care hospital in Maharashtra, India - Korde, Vaishali R.; Barse, Sharin P.; Barla, Jaya S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Thyroid dysfunction is known to be the commonest endocrinological disorder in pregnancy. A range of adverse outcomes in pregnant women and the fetus have been reported. These can be prevented if the thyroid dysfunction is diagnosed and treated as early as possible. There are limited studies conducted on the prevalence of thyroid dysfunction in pregnancy in India. Hence, this study was conducted for assessment of the prevalence of thyroid dysfunction in pregnancy. Methods: The present study is a prospective study conducted in the Department of Obstetrics and Gynecology, MIMER Medical College and Hospital, Talegaon, Dabhade, Maharashtra. The total sample population comprised of 705 pregnant women with uncomplicated singleton intra-uterine pregnancy. All participants were screened by estimation for serum TSH in first trimester. Results: The prevalence of thyroid dysfunction in the present study is 13.9%. Of this, prevalence of hypothyroidism is 12.76% and that of hyperthyroidism is 1.13%. Conclusions: With this study, we conclude that there is high prevalence of thyroid dysfunction in pregnancy even in rural population. Thus, a universal screening helps in early diagnosis and preventing the aftermaths of thyroid dysfunction in pregnancy.